Mitigasi Risiko Siklus Pengeluaran Gereja XYZ Di Tigarunggu, Sumut (XYZ Church Expenditure Cycle Risk Mitigation in Tigarunggu, North Sumatera) - Nathania Carissa Tjahja Pranata; Ika Kristianti (Akutansi Bisnis & Manajemen ( ABM ), 2022)
The financial cycle is the main activity for an organization. One of them is the cash disbursement cycle. Recording of organizational expenditure cycles is required for both for-profit and not-profit organizations. The purpose of this research is to know the importance of a risk-based audit approach in the expenditure cycle of non-profit organizations. This study uses qualitative analysis techniques. The object of this research is XYZ Church located in Tigarunggu Village, North Sumatra. The results showed that the level of inherent risk, control, and detection in XYZ Church was high. This is due to discrepancies in recording, the potential for fraudulent use of cash, discrepancies between cash and physical records, and rationalization of fraud. Internal control can be one of the Church's efforts to control the risks that occur. The implementation of low or inappropriate internal control has a high level of risk compared to the implementation of good internal control.